2021
DOI: 10.1111/jch.14173
|View full text |Cite
|
Sign up to set email alerts
|

The effect of medication on the aldosterone‐to‐renin ratio. A critical review of the literature

Abstract: The aldosterone-to-renin ratio (ARR) is a widely used screening test for primary aldosteronism (PA). However, there are various confounding factors, including medication, that may influence the levels of renin and/or aldosterone and consequently the ARR. While withdrawal of antihypertensive treatment prior to screening is advisable, this is not always practical or safe. When it is not possible to interrupt treatment, medications with a neutral, or at least a negligible effect on the ARR are required for bridgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
6
0
6
Order By: Relevance
“…In treated hypertension, almost all antihypertensive drug classes interfere with the renin angiotensin‐aldosterone system and therefore with the accurate measurement of plasma renin and aldosterone. 46 , 47 However, for safety reasons, many hypertensive patients cannot discontinue their antihypertensive drug treatment. Current guidelines recommend several classes of antihypertensive drugs that have the least influence on the renin‐angiotensin aldosterone system, such as non‐dihydropyridine calcium‐channel blockers, α1‐blockers, and direct vasodilators, as possible alternative choices of antihypertensive therapy after withdrawal of drugs that may interfere with the renin‐angiotensin aldosterone system, while screening for primary aldosteronism.…”
Section: Blood Pressure Control In Primary Aldosteronism Screenmentioning
confidence: 99%
See 1 more Smart Citation
“…In treated hypertension, almost all antihypertensive drug classes interfere with the renin angiotensin‐aldosterone system and therefore with the accurate measurement of plasma renin and aldosterone. 46 , 47 However, for safety reasons, many hypertensive patients cannot discontinue their antihypertensive drug treatment. Current guidelines recommend several classes of antihypertensive drugs that have the least influence on the renin‐angiotensin aldosterone system, such as non‐dihydropyridine calcium‐channel blockers, α1‐blockers, and direct vasodilators, as possible alternative choices of antihypertensive therapy after withdrawal of drugs that may interfere with the renin‐angiotensin aldosterone system, while screening for primary aldosteronism.…”
Section: Blood Pressure Control In Primary Aldosteronism Screenmentioning
confidence: 99%
“…Primary aldosteronism screen requires accurate measurement of plasma renin and aldosterone for the calculation of the aldosterone‐to‐renin ratio. In treated hypertension, almost all antihypertensive drug classes interfere with the renin angiotensin‐aldosterone system and therefore with the accurate measurement of plasma renin and aldosterone 46,47 . However, for safety reasons, many hypertensive patients cannot discontinue their antihypertensive drug treatment.…”
Section: Blood Pressure Control In Primary Aldosteronism Screenmentioning
confidence: 99%
“…If PAC and PRA values could be obtained at the first visit and the screening of PA could be completed before the beginning of anti-hypertension medications, we would not be bothered with the influences of medications [ 11 ]. This is important because medications recognized as less affecting PAC and PRA values actually, significantly affect these values [ 12 ]. The rapid PAC and PRA measurements would enable us to distinguish secondary aldosteronism from PA at the first visit; patients with secondary aldosteronism share the resistant hypertension and hypokalemia with PA patients as the clinical presentation, but require different approaches for screening, diagnosis, and treatment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the event that cessation of antihypertensive agents is not possible, the current Endocrine Society guidelines recommend switching to verapamil, hydralazine, or an α-adrenergic blocker such as doxazosin on the assumption that these drugs exert noto-minimal effects on the RAAS [1]. While the theoretical background for their largely neutral effect on the ARR is strong, a recent review article found that no robust studies investigating the effects of verapamil and hydralazine on the ARR have been performed [2]. Specifically, studies have usually assessed average changes in renin and aldosterone but not the individual changes in ARR.…”
Section: Introductionmentioning
confidence: 99%